Circulating desmosine levels do not predict emphysema progression but are associated with cardiovascular risk and mortality in COPD - Rabinovich, Roberto A.; Miller, Bruce E.; Wrobel, Karolina; Ranjit, Kareshma; Williams, Michelle C.; Drost,, Ellen; Edwards, Lisa D.; Lomas, David A.; Rennard, Stephen I.; Agustí, Alvar; Tal-Singer, Ruth; Vestbo, Jørgen; et al. (European Respiratory Society, 2016)
Elastin degradation is a key feature of emphysema and may have a role in the pathogenesis of atherosclerosis associated with chronic obstructive pulmonary disease (COPD). Circulating desmosine is a specific biomarker of elastin degradation. We investigated the association between plasma desmosine (pDES) and emphysema severity/progression, coronary artery calcium score (CACS) and mortality. pDES was measured in 1177 COPD patients and 110 healthy control subjects from two independent cohorts. Emphysema was assessed on chest computed tomography scans. Aortic arterial stiffness was measured as the aortic–femoral pulse wave velocity. pDES was elevated in patients with cardiovascular disease (p<0.005) and correlated with age (rho=0.39, p<0.0005), CACS (rho=0.19, p<0.0005) modified Medical Research Council dyspnoea score (rho=0.15, p<0.0005), 6-min walking distance (rho=−0.17, p<0.0005) and body mass index, airflow obstruction, dyspnoea, exercise capacity index (rho=0.10, p<0.01), but not with emphysema, emphysema progression or forced expiratory volume in 1 s decline. pDES predicted all-cause mortality independently of several confounding factors (p<0.005). In an independent cohort of 186 patients with COPD and 110 control subjects, pDES levels were higher in COPD patients with cardiovascular disease and correlated with arterial stiffness (p<0.05). In COPD, excess elastin degradation relates to cardiovascular comorbidities, atherosclerosis, arterial stiffness, systemic inflammation and mortality, but not to emphysema or emphysema progression. pDES is a good biomarker of cardiovascular risk and mortality in COPD.Elastin degradation is a hallmark of emphysema and may have a role in the pathogenesis of atherosclerosis with COPD http://ow.ly/Y9GsC